2008
DOI: 10.1186/1471-2148-8-270
|View full text |Cite
|
Sign up to set email alerts
|

Key biosynthetic gene subfamily recruited for pheromone production prior to the extensive radiation of Lepidoptera

Abstract: BackgroundMoths have evolved highly successful mating systems, relying on species-specific mixtures of sex pheromone components for long-distance mate communication. Acyl-CoA desaturases are key enzymes in the biosynthesis of these compounds and to a large extent they account for the great diversity of pheromone structures in Lepidoptera. A novel desaturase gene subfamily that displays Δ11 catalytic activities has been highlighted to account for most of the unique pheromone signatures of the taxonomically adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 56 publications
1
76
0
Order By: Relevance
“…This suggests that the genetic architecture for the production of all hydrocarbons was already present in ancestral ants, and has been maintained throughout their subsequent vast radiation. This parallels the finding that the key biosynthetic gene subfamily used in pheromone production existed prior to the radiation of Lepidoptera (Liénard et al 2008). Although few species currently appear to synthesize this type of complex CHC profiles, a recent study that used high temperature (HT) columns to analyze CHC profiles of two species of tropical ants (Menzel et al 2008) found that Crematogaster modiglianii and Camponotus rufifemur produce 14 methylalkenes, all of which occurred at chain-lengths greater than C 34 .…”
Section: Resultssupporting
confidence: 66%
“…This suggests that the genetic architecture for the production of all hydrocarbons was already present in ancestral ants, and has been maintained throughout their subsequent vast radiation. This parallels the finding that the key biosynthetic gene subfamily used in pheromone production existed prior to the radiation of Lepidoptera (Liénard et al 2008). Although few species currently appear to synthesize this type of complex CHC profiles, a recent study that used high temperature (HT) columns to analyze CHC profiles of two species of tropical ants (Menzel et al 2008) found that Crematogaster modiglianii and Camponotus rufifemur produce 14 methylalkenes, all of which occurred at chain-lengths greater than C 34 .…”
Section: Resultssupporting
confidence: 66%
“…Species-specific moth pheromone biosynthetic Δ11-desaturases have likely evolved from the metabolic acyl-CoA Δ9-desaturases (Roelofs and Rooney, 2003;Liénard et al, 2008). They catalyze the formation of uncommon unsaturated fatty-acyl-CoA esters with variable chain lengths, different locations of unsaturations, and either the ordinary Z or the unusual E double bond geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Δ12 mFADs have also been identified, but they are involved in primary metabolism during the production of methylene-interrupted PUFAs [31] rather than pheromone biosynthesis. The moth mFADs can also introduce a double bond at the terminal position between the penultimate and ultimate carbon atoms [78,83] and can produce FAs with a system of isolated double bonds [64] or a system of conjugated double bonds [10,65,66,76,79,80,82]. Among the more bizarre desaturation reactions, an mFAD identified in the processionary moth, Thaumetopoea pityocampa, can introduce triple bonds into the FA chains [81], resembling in activity an mFAD described in the plant of Crepis genus [84].…”
Section: Mfad Propertiesmentioning
confidence: 99%
“…The FA-derived pheromones are the most common [8], encompassing thousands of compounds and mixtures of compounds [9]. Insect pheromone-biosynthetic enzymes presumably evolved via a divergence of the original functions of the FA-biosynthetic and FA-modifying enzymes participating in insect primary metabolism [10]. The diversification of the pheromone-biosynthetic enzymes likely has been driven by evolutionarily imposed requirements on sex pheromone signal specificity [11,12].…”
Section: Introductionmentioning
confidence: 99%